The Commercialisation of Modern Islamic Insurance Providers: A Study of Takaful Business Frameworks in Malaysia - Kamaruzaman Noordin; Mohd. Rijal Muwazir @Muzakir; Azian Madun (International Journal of Nusantara Islam, 2014)
A commercial insurance contract is deemed invalid by many Muslim scholars due to the fact that it is a mu`awada (financial exchange) contract, which is overwhelmed by prohibited elements such as gharar (uncertainty), riba (interest), and maysir (gambling). As an alternative, a Shari`acompliant insurance scheme (also known as takaful) that supposedly run on the principles of mutual co-operation was proposed by the scholars and subsequently institutionalized in the late 1970s. Nevertheless, after more than 30 years, it appears that the majority of takaful operators currently exist worldwide were established as joint-stock or public limited companies (PLCs). As a result, it could be argued that the original concept of takaful was later overshadowed by the element of profit-making as observed in commercial insurance entities. This paper therefore sets out to examine those issues, which directly relate to this form of commercialisation. It argues that since the establishment of insurance companies based on commercial framework is impermissible, it could possibly affect the validity of present takaful arrangement. This study is mainly qualitative and relies greatly upon the documentation method. It is also based on afieldwork method, since the business models adopted by several takaful operators in Malaysia are carefully examined. In general, it is found that the characteristics of a commercial takaful entity may not necessarily be similar to that of its conventional counterpart.